Variants of anatomical organization of the maxillary molars in reference to the maxillary sinus - A. S. Opravin; A. S. Zykova; T. A. Kudryavtsev; L. N. Kuzmina; A. S. Galieva (Эндодонтия Today)
INTRODUCTION. Balance between the floor of the maxillary sinus (MS) and the maxillary molars roots is of clinical significance. In cases where the root ends are located inside the sinuses, or very close to the bottom of the maxillary sinus, tooth extraction, apical surgery and some conservative endodontic manipulations can lead to a number of complications: perforation of the maxillary sinus floor, formation of an oroantral fistula, extrusion of a tooth root fragment into the maxillary sinus. AIM. To conduct a systematic review of original research studies on the anatomical variations of maxillary molar roots and their spatial relationship to the maxillary sinus. MATERIALS AND METHODS. A systematic review of scientific articles and original studies included in international and domestic databases was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) checklist. RESULTS. 46 articles containing data from randomized controlled clinical trials, longitudinal, and cohort studies were selected for screening. 28 references were submitted, of which 5 were excluded due to high risk of bias. As a result, 23 studies were included in the systematic review. RESULTS. There are three main categories of interactions between the maxillary molars and the maxillary sinus floor: type 1 – the root apices do not reach the maxillary sinus; type 2 – the maxillary sinus floor contacts the root apex; type 3 – the root apex enters the maxillary sinus cavity. The most common type of relationship between the upper molar roots and the maxillary sinus is type 1. The smallest distance was determined from the buccal root apices of the second molars to the maxillary sinus floor (0.8±2.5 mm). The volume of the maxillary sinus depended on age and increased until the age of 20, and then gradually decreased. CONCLUSIONS. The data contained in the analyzed studies can be of significant help to dentists in planning surgical and endodontic interventions on the molars of the upper jaw, which will prevent serious complications associated with the anatomical features of correlation of root apices of the lateral teeth group and the maxillary sinus.